(untitled) - Brown, Marc Tolon (Boston, 1979)
His friends tease Arthur when he gets glasses, but he soon learns to wear them with pride.
Richter Elem Accel. Reader
2.3
Keywords: Eyeglasses; Fiction; Animals; Fiction; School stories